Political legitimacy in Japan: a Luhmannian perspective - Mitchell, Andrew (Journal of Sociocybernetics, 2016)
Despite widespread public opinion against many of his policies, Abe Shinzo’s Liberal Democratic Party (LDP) is not only maintaining its electoral success but expanding on it. Furthermore the LDP has been in almost continual power since 1955, making Japan in the eyes of some a de facto one-party state. This paper will explore the question of legitimacy in Japan’s political system, especially the ones raised by Karel van Wolferen the 1980s, and whether the current power structure can be considered to hold it. Through using Niklas Luhmann’s social systems theory, in particular his concept of political legitimacy, it will be shown that while electoral reforms in 1994 addressed most of the systemic legitimacy issues in Japan’s political system, a potential deficit in the government/opposition coding remains.